Antiphospholipid Syndrome in Chronic Thromboembolic Pulmonary Hypertension: A Well-Defined Subgroup of Patients - Jiang, Xin; Du, Yao; Cheng, Chun-Yan; Denas, Gentian; Zhou, Yu-Ping; Wu, Tao; Zhang, Yi-Xin; Han, Zhi-Yan; Pengo, Vittorio; Jing, Zhi-Cheng (Thrombosis and Haemostasis, 2019)
Antiphospholipid syndrome (APS) is an acquired thrombophilia with an uncertain role in the development of chronic thromboembolic pulmonary hypertension (CTEPH). We aimed to assess the association of APS with the clinical phenotype of CTEPH. We retrospectively reviewed data of CTEPH patients referred to our center. Clinical, angiographic, and hemodynamic data were available for all patients. APS was diagnosed in the presence of one or more positive antiphospholipid (aPL) tests confirmed more than 12 weeks apart. Data were compared between APS-positive and APS-negative patients. From May 2013 to December 2018, 297 patients with CTEPH were enrolled. Twenty-three (7.7%) were positive for laboratory tests exploring aPL antibodies. Among them, 17 patients (74%) had a triple positive aPL profile. When compared with the APS-negative group, APS patients were significantly younger (30.0 ± 11.1 vs. 55.6 ± 12.9 years, p < 0.0001), had more frequently a history of pulmonary embolism (95.6% vs. 65.7%, p = 0.003), and had more frequently associated autoimmune disease (43.5% vs. 2.9%, p < 0.0001). In APS-positive patients, pulmonary artery lesions were more proximal and hemodynamic profiles were less compromised. Our results show that patients with APS are a unique group of CTEPH patients with well-defined clinic and hemodynamic characteristics.
Keywords: antiphospholipid antibodies; chronic thromboembolic pulmonary hypertension; antiphospholipid syndrome